Interprofessional education to support alcohol use screening and future team-based management of stress-related disorders in vulnerable populations - Fitzpatrick-Schmidt, Taylor; Edwards, Scott (Frontiers in Education, 2024)
Alcohol use disorder (AUD) is a psychiatric disease that affects approximately 10% of the population. Individuals suffer from a myriad of causes and consequences of AUD, and teambased management of patients is often required for given the chronic and complex nature of the disease. Interprofessional education (IPE) for biomedical science and health professional students that incorporates patient-centered cases focused on AUD and adjacent stress-related disorders may improve future collaboration in managing these conditions and community outcomes related to wellbeing. This study assessed the impact of a single, 90-minute IPE exercise on improving confidence in possessing the knowledge and skills required for screening and management of patients at risk for AUD, the role of social determinants in health and stressrelated diseases, and the importance of supporting the mental health of professionals to improve patient care. The exercise was provided to three groups of post-baccalaureate students (physician assistant [PA], physical therapy [PT], and biomedical sciences [BMS] graduate programs) within a human physiology course. Pre-and post-test surveys were administered via web-based platform before and after the session. We found significant improvements in responses to seven of the eight assessment questions, including improved knowledge of one's role in biomedical research or brief interventions for alcohol misuse, increased confidence in advising patients and community members about responsible alcohol drinking, and improved understanding of the role of all three professions (PA, PT, and BMS) in managing, treating, or researching stress-related disorders. These findings suggest that a single focused IPE session is impactful for improving student knowledge and understanding of stress-related disorders. IPE may represent an important educational strategy to bring together future scientists and health professionals to reflect upon unique and shared knowledge bases as well as integrative care principles for both patient and professional wellbeing.